Preparation of yttria powders co-doped with Nd3+, and La3+ using EDTA gel processes for application in transparent ceramics. Issue 13 (October 2017) - Kruk, A.; Wajler, A.; Bobruk, M.; Adamczyk, A.; Mrózek, M.; Gawlik, W.; Brylewski, T.
Abstract: The aim of the work was to synthesize Y2 O3, La0.1 Y1.9 O3, Nd0.1 Y1.9 O3, Nd0.1 La0.1 Y1.8 O3 and Nd0.12 La0.1 Y1.78 O3 powders using EDTA gel processes, and to examine the physicochemical properties of transparent sinters obtained from these powders. A part of this goal was the determination of the influence of various dopants on the optical properties of yttria. X-ray diffraction studies of the investigated powders and sinters confirmed their single-phase composition, which indicated incorporation of lanthanum and neodymium into the crystal lattice of yttria. Scanning electron microscopy (SEM) combined with density measurements indicated that the studied sinters had high density. An optical transparency over 50% was obtained for the Y2 O3 sinter in the wavelenght range of 450–1100 nm. The influence of dopants on the level of transmittance was also investigated.